Always Coming Home: Territories of Relation and Reparative Archives - Christen, Kim; Pinkham, Josiah; Hooee, Cordelia; Wilson, Amelia (Archivaria, 2022)
This article contributes to person-centred archival praxis and methodology by providing a reparative theoretical framework based in Indigenous relationships to kin, territories, material belongings, and systems of knowledge to unsettle standard archival practices. By foregrounding the stories of Indigenous archivists and practitioners, through their own narratives, we build on Indigenous theory as story work to interrogate archival systems, workflows, and policies that continue to replay settler-colonial tactics of removal and epistemic violence. In order to restructure archival practices, we suggest that institutions need to build relationship infrastructures that allow for respectful archival listening, shared stewardship, and return practices that go beyond mere exchange. Instead, to centre Indigenous knowledge systems and practices, archival practices must not only acknowledge territorial, intellectual, and cultural sovereignty but must also enact mechanisms for their realization.